Gradual transitions in morphology of diamond films grown by using N-2 admixtures of CH4+H-2 gas in a hot filament assisted chemical vapour deposition system - Kshirsagar, S. T.; Kshirsagar, R. B.; Patil, P. S.; Kulkarni, A.; Mandate, A. B.; Gaikwad, A. B.; Gokhale, Suresh P. (Diamond and Related Materials, 2005)
A study of the evolution of morphology of diamond films grown as a function of N-2 gas additions to the CH4+H-2 precursor in an HF-CVD system is presented. With the increase of admixture of N2 fraction, in contrast to earlier studies, the morphology was observed first to gradually change from {111}-faceted crystallites texture to that of an intermediate cubo-octahedral crystallite texture and then gradually but finally to transform completely into that of {100}-faceted crystallites. The threshold nitrogen concentration, [N-2](thr), required to bring about the said transition in morphology was much larger than it was reported previously. Moreover, the morphology transition required a larger [N-2](thr) when a large fraction of methane was employed. Further additions of nitrogen, that just exceeded the [N-2](thr), resulted in growth of films containing slightly bigger {100}-multi-layered grains or isolated planar {100}-platelets. For extremely large nitrogen additions, the growth of nanocrystalline or amorphous carbon films was observed. The N-2 additions more than 50 vol.% did not yield any deposition. Raman scattering and photoluminescence measurements were used respectively for characterizing the quality and nitrogen doping in the films. These results are attributed to the possible catalytic role of atomic nitrogen at the growing surface. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: diamond film; hot filament CVD; morphology transitions; nitrogen

Polymerization in surfactant liquid crystalline phases - Wadekar, M. N.; Pasricha, R.; Gaikwad, A. B.; Kumaraswamy, Guruswamy (Chemistry of Materials, 2005)
We report the formation of cross-linked polysiloxane particles having rodlike and sheetlike morphologies by condensation of monomers in organized liquid crystalline mesophases of nonionic surfactants. The characteristic diffraction pattern obtained from the liquid crystalline surfactant assembly is preserved during polymer synthesis. The polymer colloids are rodlike when synthesized in a hexagonal mesophase and are sheetlike when synthesized in a lamellar mesophase. Interestingly, the size of the polymer particles is on the order of micrometers, viz. 3 orders of magnitude larger than the characteristic size of the surfactant mesophase. Thus, the polymers phase separate from the liquid crystalline phase during polymerization, and organize to resemble the mesophase geometry. The polymer particles are organized so as to minimize the elastic distortion of the surfactant mesophase after they phase separate. We speculate that the observed particle morphologies are formed due to the slow kinetics of polycondensation under our experimental conditions.

TiO2 ceramic varistor modified with tantalum and barium - Gaikwad, A. B.; Navale, SC; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
The non-linear current (I)-voltage (V) characteristics of titanium dioxide doped with small quantities of tantalum and barium (99.9 TiO2 + 0.1 Ta and 99.4 TiO2 + 0.1 Ta + 0.5 Ba, all are in at.%) were investigated. These samples have the non-linear coefficient (alpha) values of (20-30) with high breakdown voltages (E-B similar to 400-700 V mm(-1)). The pentavalent tantalum acts as donor and increases the electronic conductivity. The higher electrical conductivity and decrease in the breakdown field strength with barium addition is attributed to higher density. The acceptor like surface states formed by barium ions segregate to grain boundaries due size misfit to thereby modifying the electrical barrier characteristics of grain boundaries. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Oxides; TiO2; varistor; X-ray diffraction

Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

Coprecipitation technique to prepare LiTaO3 powders - Navale, SC; Gaikwad, A. B.; Ravi, V (Materials Letters, 2006)
A simple coprecipitation technique had been successfully applied for the preparation of pure ultrafine single phase LiTaO3 (LT). An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Li+ and Ta5+ cations as carbonate and hydroxide respectively. This precursor oil heating at 750 degrees C produces LT powders. For comparison, LT powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Coprecipitation technique to prepare NaNbO3 and NaTaO3 - Samuel, V; Gaikwad, A. B.; Ravi, V (Bulletin of Materials Science, 2006)
A simple coprecipitation technique has been used successfully for the preparation of pure, ultrafine, single phases of NaNbO3 (NN) and NaTaO3 (NT). An alcoholic solution of ammonium carbonate and ammonium hydroxide was used to precipitate Na+ and Nb5+ (or Ta5+) cations under basic conditions as carbonate and hydroxide, respectively. On heating at 700 degrees C, these precursors produce respective products. For comparison, both NN and NT powders were also prepared by the traditional solid state method. The phase purity and lattice parameters were studied by powder X-ray diffraction (XRD). The particle size and morphology were studied by scanning electron microscopy (SEM).
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction

Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Electrochemical polymerization of o-anisidine on low carbon steel from aqueous salicylate solution: corrosion protection study - Wankhede, M. G.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
The electrochemical polymerization of o-anisidine was carried out on low carbon steel from an aqueous salicylate medium using cyclic voltammetry. The resulting poly(o-anisidine) coatings were uniform and adherent to the steel substrates. These coatings were characterized by cyclic voltammetry, LTV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction measurements and scanning electron microscopy. The ability of the poly(o-anisidine) coatings to protect low carbon steel in an aqueous 3% NaCl was evaluated by the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(o-anisidine) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; low carbon steel; poly(o-anisidine) coatings

Electrochemical synthesis of corrosion protective polyaniline coatings on mild steel from aqueous salicylate medium - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Science and Technology of Advanced Materials, 2006)
Strongly adherent polyaniline coatings were electrochemically synthesized on mild steel from an aqueous salicylate medium. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The extent of the corrosion protection offered by polyaniline coatings to mild steel was investigated in aqueous 3% NaCl solution, 0.01 M Na2SO4 Solution and in aqueous solutions of NaCl + Na2SO4 with different concentrations by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies reveal that the corrosion resistance of the polyaniline-coated mild steel is significantly higher and the corrosion rate is considerably lower than that of uncoated steel. (c) 2006 Published by NIMS and Elsevier Ltd.
Keywords: Conducting polymer coatings; corrosion protective coatings; cyclic voltammetry; Electrochemical polymerization; polyaniline coatings mild steel

Poly(o-toluidine) coatings on copper: electrochemical synthesis from aqueous media - Shinde, V.; Mandale, A. B.; Patil, K. R.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
Poly(o-toluidine) (POT) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-toluidine using aqueous sodium oxalate solution as supporting electrolyte. The resulting coatings were uniform, compact and strongly adherent to the Cu substrate. These coatings were characterized by using cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) measurements and X-ray photoelectron spectroscopy (XPS). The results of these studies reveal that the sodium oxalate is suitable supporting electrolyte for the electrochemical polymerization of o-toluidine on Cu substrate. It is found that the electrochemical polymerization of o-toluidine takes place after the passivation of the Cu substrate via formation of copper oxalate (CuC2O4, H2O) layer, which is confirmed by XRD and XPS. The optical absorption spectroscopy study reveals the exclusive formation of the pernigraniline base (PB) form of POT. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Synthesis and characterization of corrosion protective poly(2,5-dimethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Applied Surface Science, 2006)
Poly(2,5-dimethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of 2,5-dimethylaniline in aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly (2,5-dimethylaniline) coatings on Cu substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique. The results of the potentiodynamic polarization demonstrate that the poly(2,5-dimethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(2,5-dimethylaniline) coated Cu than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 5-dimethylaniline) coatings; conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Poly(2

Synthesis of MgNb2O6 by coprecipitation - Navale, S. C.; Gaikwad, A. B.; Ravi, V. (Materials Research Bulletin, 2006)
A simple coprecipitation technique was used successfully to synthesize fine powders of MgNb2O6 (MN) phase. An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Mg2+ and Nb5+ cations as carbonate and hydroxide respectively under basic conditions. This precipitate on heating at 750 degrees C produced MN powders. For comparison MN powders were prepared by the traditional solid state method. The phase content and the lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology of the particles were studied by scanning electron microscopy (SEM). (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction

Synthesis of star shaped Ba1-xSrTiO3 (BST) powders - Khollam, Y. B.; Potdar, H. S.; Deshpande, S. B.; Gaikwad, A. B. (Materials Chemistry and Physics, 2006)
Uniform star shaped strontium substituted barium titanyl oxalate Ba1-xSrxTiO(C2O4)(2) (BSTO)/strontium substituted barium titanate, Ba1-xSrxTiO3 (BST) powders were prepared via a simple chemical co-precipitation route with x = 0.15, 0.20, and 0.25. The process involved an addition of 0.1 M solution of titanium tetrabutoxide (BTM) in isopropanol (IPA) to 0.1 M oxalic acid in IPA containing 0.2 M of H2O to produce titanyl oxalate precipitate which was further reacted with 0.1 M solution of ammonium oxalate to obtain 0.1 M clear homogeneous solution of ammonium titanyl oxalate (ATO) with pH 4.25 containing titanium in the form of soluble anionic oxalate species [TiO(C2O4)(2)(2-)]. Stoichiometric quantities of barium hydroxide and strontium nitrate were dissolved in distilled water and its pH was adjusted nearly equal to that of ATO (similar to 4.15) by drop wise addition of dilute HNO3 solution 1:10 (v/v). The addition of this mixed cation precursor solution to ATO solution resulted in precipitation of strontium substituted barium titanyl oxalate (BSTO) having star shaped morphology. The calcination of BSTO precursors at 730 degrees C for 4 h in air produced cubic BST powders (a(o) similar to 4.001, 3.996 and 3.991 angstrom for x = 0. 15, 0.20, 0.25, respectively) having star shaped morphology. SEM, XRD and IFTIR techniques were used to characterize the BSTO/BST powders. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; capping agent; Co-precipitation; Morphology

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Co-precipitation technique to prepare BaTa2O6 - Navale, S. C.; Samuel, Violet; Gaikwad, A. B.; Ravi, V. (Ceramics International, 2007)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate barium and tantalum ions as barium oxalate and tantalum hydroxide under basic conditions. On calcination at 750 degrees C, this precursor yielded BaTa2O6 (BT) ceramics. This is much lower temperature as compared to that prepared by traditional solid-state method (1000 degrees C) as reported for the formation of BaTa206. Transmission electron microscope (TEM) investigations revealed that the average particle size is 70 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 100. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: barium tantalate; Ceramics; Electron microscopy; Oxides; X-ray diffraction

Coprecipitation technique to prepare CoTa2O6 and CoNb2O6 - Mulla, Imtiaz S.; Natarajan, N.; Gaikwad, A. B.; Samuel, V.; Guptha, U. N.; Ravi, V. (Materials Letter, 2007)
An aqueous solution of sodium hydroxide was used to coprecipitate cobalt and tantalum (or niobium) ions from their precursors as hydroxides under basic conditions. This precipitate yielded CoTa2O6 (CT) or CoNb2O6 (CN) ceramics on calcining at 700 degrees C, i.e. at a temperature much lower than 900 degrees C, reported for the formation of these powders prepared by the traditional solid state method. The X-ray diffraction (XRD) studies were employed to investigate phase contents and lattice parameters. The morphology of the synthesized powders was investigated by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Oxides; X-ray methods

Coprecipitation technique to prepare NiNb2O6 - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Natarajan, N.; Ravi, V. (Materials Letter, 2007)
A mixture of ammonium carbonate and ammonium hydroxide was used to coprecipitate nickel and niobium ions as nickel carbonate and niobium hydroxide under basic conditions. This precursor yielded NiNb2O6 (NN) ceramics on calcining at 700 degrees C (at a temperature lower than 800 degrees C which is necessary for the formation of NiNb2O6 when prepared by the traditional solid state method). The average particle size and morphology of these powders were investigated by transmission electron microscope (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Corrosion protection aspects of electrochemically synthesized poly(o-anisidine-co-o-toluidine) coatings on copper - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Electrochimica Acta, 2007)
The poly(o-anisidine-co-o-toluidine) coatings were synthesized on copper substrates by electrochemical copolymerization of o-anisidine with o-toluidine using sodium salicylate as supporting electrolyte. These coatings were characterized by cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR) and scanning electron microscopy (SEM). The formation of the copolymer with the mixture of monomers in the aqueous sodium salicylate solution was ascertained by a critical comparison of the results obtained with the polymerization of the individual monomers, o-anisidine and o-toluidine, respectively. The corrosion protection aspects of poly(o-anisidine-co-o-toluidine) coatings to copper was investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of the potentiodynamic polarization measurements and EIS studies showed that the poly(o-anisidine-co-o-toluidine) coatings provided the effective corrosion protection to copper than that of respective homopolymers. The corrosion rate is observed to depend on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: copolymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-anisidine-co-o-toluidine)

Low temperature route to prepare LaFeO3 and LaCoO3 - Jadhav, A. D.; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Materials Letters, 2007)
A combination of digestion and further low temperature calcination to crystallize the product was employed to prepare LaFeO3 (LF) and LaCoO3 (LC) powders. Freshly co-precipitated lanthanum and ferric (or cobalt) hydroxide gels by sodium hydroxide were allowed to react at 100 degrees C under refluxing and stirring conditions for 4-6 h. These oven dried powders were heated at 450 degrees C to from crystalline LF (or LC) powders. The phase contents and lattice parameters were investigated by X-ray diffraction (XRD). Transmission electron microscope (TEM) investigations were carried out to examine the morphology and average particle size of these powders. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; LaFeO3; Precipitation; transmission electron microscopy; X-ray diffraction

Novel technique to prepare LiNbO3 at low temperature - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Mirji, S. A.; Ravi, V. (Materials Letter, 2007)
Fresh niobium hydroxide was first precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and niobium hydroxides together and heating at a low temperature (400 degrees C) produced pure ultrafine single phase LiNbO3 (LN). In the literature, this is the lowest temperature so far reported on the formation of LN. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; LiNbO3; X-ray diffraction

Poly(o-anisidine) films on mild steel: electrochemical synthesis and biosensor application - Patil, Dewyani; Gaikwad, A. B.; Patil, Pradip (Journal of Physics D-Applied Physics, 2007)
Poly(o-anisidine) (POA) films were synthesized on mild steel from an aqueous oxalic acid solution by electrochemical polymerization of o-anisidine using cyclic voltammetry. These films were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The enzyme glucose oxidase (GOx) was entrapped into the POA film by a physical adsorption method. The resulting POA-GOx films were characterized by UV-visible absorption spectroscopy, FTIR and SEM. The amperometric response of the POA-GOx films was measured as a function of glucose concentration in phosphate buffer solution (pH 7.3). The POA-GOx films exhibited a fast amperometric response (1-5 s) and a linear response in the range of 2-20 mM glucose. The maximum current density and Michaelis-Menten constant of POA/GOx films were found to be similar to 406 mu A cm(-2) and 1.03 mM, respectively. The shelf stability, operational stability and thermal stability of these films were also investigated.

Preparation of nanocrystalline ferroelectric CaBi4Ti4O15 by citrate gel method - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Ceramics International, 2007)
A gel was formed when an aqueous solution of CaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced nano crystallites of the ternary oxide, CaBi4Ti4O15 (CBT). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 390. The ferroelectric hysteresis loop parameters of these samples were also studied by a home-built Sawyer-tower circuit. (c) 2006 Elsevier Ltd and Techna Group S.H. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides

Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Synthesis and corrosion protection study of poly(o-ethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Surface & Coatings Technology, 2008)
Poly(o-ethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-ethylaniline in an aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethylaniline to generate strongly adherent and smooth poly(o-ethylaniline) coatings on Cu substrates. The performance of poly(o-ethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies demonstrate that the poly(o-ethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(o-ethylanitine) coated Cu (similar to 15 mu m thick) than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 70. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings

Poly(o-anisidine) coatings on brass: synthesis, characterization and corrosion protection - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Current Applied Physics, 2009)
Poly(o-anisidine) (POA) coatings were synthesized on brass by electrochemical polymerization of o-anisidine in aqueous salicylate solution by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy., Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The corrosion protection aspects of POA coatings on brass in aqueous 3% NaCl solution were investigated by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The potentiodynamic polarization measurements show that the POA coating has ability to protect the brass against corrosion. The corrosion potential was about 0.204 V versus SCE more positive for the POA coated brass than that of uncoated brass and reduces the corrosion rate of brass almost by a factor of 800. The corrosion behavior of the POA coatings was also investigated by EIS through immersion tests performed In aqueous 3% NaCl solution. The evolution of the impedance parameters with the immersion time was studied and the results Show that the POA acts as a protective coating on brass against corrosion in 3% NaCl solution. The water uptake and delamination area were also determined to further support the corrosion protection performance of the POA coating. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: brass; conducting polymers; Corrosion resistant coatings; cyclic voltammetry; Electrochemical impedance spectroscopy; Electrochemical polymerization; poly(o-anisidine)

Monitoring structural defects and crystallinity of carbon nanotubes in thin films - Mahajan, S. S.; Bambole, M. D.; Gokhale, S. P.; Gaikwad, A. B. (Pramana-Journal of Physics, 2010)
We report the influence of catalyst formulation and reaction temperature on the formation of carbon nanotube (CNT) thin films by the chemical vapour deposition (CVD) method. Thin films of CNTs were grown on Fe-Mo/Al(2)O(3)-coated silicon wafer by thermal decomposition of methane at different temperatures ranging from 800 to 1000A degrees C. The electron microscopic investigations, SEM as well as HRTEM, of the as-grown CNT thin films revealed the growth of uniform multi-walled CNTs in abundance. The intensity ratio of D-band to G-band and FWHM of G-band through Raman measurements clearly indicated the dependency of structural defects and crystallinity of CNTs in thin films on the catalyst formulation and CVD growth temperature. The results suggest that thin films of multi-walled CNTs with negligible amount of defects in the nanotube structure and very high crystallinity can be obtained by thermal CVD process at 925A degrees C.
Keywords: Carbon nanotubes; chemical vapour deposition; Raman spectroscopy; scanning electron microscopy; Thin films

Synthesis and corrosion protection aspects of poly(o-toluidine)/CdO nanoparticle composite coatings on mild steel - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Journal of Coatings Technology and Research, 2010)
This study examines the possibility of using poly(o-toluidine)/CdO (POT-CdO) nanoparticle composite coating for corrosion protection of mild steel in chloride environment. The POT-CdO nanoparticle composite coating was synthesized on mild steel from aqueous tartrate solution containing CdO-nanoparticles (size similar to 18 nm) by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-Visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction measurements. The corrosion protection aspects of the resulting POT-CdO nanocomposite structure were investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of these investigations reveal that the POT-CdO nanoparticle composite acts as a protective coating on mild steel and reduces the corrosion rate of mild steel almost by factor of 70.
Keywords: CdO; Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Mild steel; Nanocomposites; Poly(o-toluidine)

Development of non-woven nanofibers of egg albumen-poly (vinyl alcohol) blends: influence of solution properties on morphology of nanofibers - Rathna, Gundloori Venkata Naga; Jog, Jyoti Prakash; Gaikwad, A. B. (Polymer Journal, 2011)
Egg albumen (EA), a highly functional globular protein with desirable properties, is the least-explored material for biomaterial applications, although it is available in abundance. In our studies, we explored the viability of EA and various blends with biocompatible and non-toxic poly (vinyl alcohol) (PVA) to produce nanofibers for biomedical applications. EA and PVA blends were prepared in various compositions. Electrospinning was used to fabricate non-woven nanofibers. Solution properties, such as viscosity and electrical conductivity, were evaluated for various prepared solutions. Solution viscosity increased with increasing polymer concentration. Solutions with higher contents of EA recorded increased conductivity, which decreased with increasing PVA content. The influence of solution properties on the morphological appearance of as-spun products was studied using scanning electron microscopy. Instead of nanofibers, nanoparticles and microparticles of EA were produced at even higher contents. In contrast, a gradual increase in the addition of PVA content to 8% EA solution resulted in the transformation of particles from large agglomerates to very fine fibers (approximate to 100nm in diameter) because of the influence of polymer content, viscosity and conductivity. The polymer-polymer interactions in the prepared materials have been validated by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and gel electrophoresis. Polymer Journal (2011) 43, 654-661; doi:10.1038/pj.2011.34; published online 18 May 2011
Keywords: Biocompatibility; biodegradable; blends; nanotechnology; Proteins

Electrical behavior of silver particulate films deposited on 8 MeV electron beam irradiated softened polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Journal of Materials Science-Materials in Electronics, 2011)
Results of the investigations carried out on the electrical behavior of silver particulate films deposited on electron beam irradiated polystyrene (PS) coated substrates held at a temperature of 455 K in a vacuum of 8 x 10(-6) torr at a constant deposition rate of 0.4 nm/s are reported. It is known that when metals are evaporated on to softened polymer substrates, subsurface particulate structures are formed whose morphology is dependent on deposition parameters. Further, it was shown that the morphology is dependent on polymer-metal interaction. The present work demonstrates that the polymer-metal interaction can be brought about in inert polymers like PS by electron irradiation. The results indicate that the films deposited on PS irradiated to a dose of 20 and 25 kGy gives rise to smaller clusters with smaller inter-cluster separation, better suited for sensor applications. The induced polymer-metal interaction is attributed to the creation of free radicals due to the 8 MeV electron irradiation.

Morphological changes in nanoparticulate silver films due to electron beam irradiation of polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions With Materials and Atoms, 2011)
Results of the studies on the effect of 8 MeV electron beam irradiation of polystyrene substrates on the morphology of silver particulate films deposited at 455 K in a vacuum of 8 x 10(-6) Torr are reported. Optical absorption studies show the presence of transverse and longitudinal plasmon resonance for films deposited on irradiated polystyrene. Scanning electron microscopy reveals a decrease in particle size with smaller inter-particle separation for irradiated films. Larger clusters are formed in the case of films deposited on polystyrene after 300 h of irradiation. In this paper, we show that the morphology of silver nanoparticulate films can be modified by electron irradiation of inert polymer substrates like polystyrene. The change observed due to irradiation is attributed to the formation of free radicals, thereby altering the polymer-metal interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electron bombardment; Optical properties; Particulate films; Polymers; Silver; surface morphology

One-step in situ synthesis of NHx-adsorbed rhodium nanocrystals at liquid-liquid interfaces for possible electrocatalytic applications - Patil, V. S.; Krishna, S. R.; Hawaldar, Ranjit R.; Gaikwad, A. B.; Sathaye, S. D.; Patil, K. R. (Journal of Colloid and Interface Science, 2011)
Nearly monodisperse rhodium nanoparticles with adsorbed NHx were synthesized at the CCl4-water interface. The presence of NHx-adsorbed species was confirmed by energy-dispersive X-ray analysis (EDX) and X-ray photoelectron spectroscopy (XPS) studies. The synthesis of controlled size 2-38 nm rhodium particles was studied as a function of reducing agent concentration by transmission electron microscopy (TEM). HRTEM confirmed the formation of rhodium nanoparticles having fringe spacing consistent with reported Rh (1 1 1) planes. The continuity of these films over an area of 1 x 1 pm was revealed by atomic force microscopy (AFM) studies. The electrocatalytic application of these nanostructure Rh-NHx), thin films for formaldehyde oxidation in 0.5 M NaOH was investigated by cyclic voltammetry. The Rh nanoparticles formed by the present strategy are expected to be useful for other catalytic applications also. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrazine hydrate; Liquid-liquid interface; Nanoparticles; Rhodium; Thin films

Structural and surface morphological properties of chemically deposited Mo0.5W0.5S2 thin film - Patil, A. A.; Hankare, P. P.; Gaikwad, A. B.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2012)
Preparation of layered type semiconductor Mo0.5W0.5S2- thin films has been successfully done by using chemical bath deposition method. Objective of the studies are related to structural, optical, morphological and electrical properties of the thin films. The preparation method is based on the reaction between tartarate complex of Mo and W with thiourea in an aqueous alkaline medium at 363 K. X-Ray diffraction reveals a polycrystalline film composed of both MoS2 and WS2 phases. The optical study shows that the band gap of the film is 1.6 eV. Electrical conductivity is high which is in the order of 10(-3)-10(-2) (Omega cm)(-1).

Preparation and characterization of silver particulate films on softened polystyrene and poly(4-vinylpyridine) blends - Gurumurthy, S. C.; Pattabi, Manjunatha; Krishna, Shreedhar; Gaikwad, A. B. (Journal of Materials Science-Materials In Electronics, 2014)
Results of the investigations carried out on the optical properties of silver particulate films deposited at a rate of 0.4 nm/s on softened polystyrene and poly(4-vinylpyridine) (P4VP) blends held at 455 K are reported. Under the conditions of deposition, a sub-surface particulate structure is expected. It had been shown earlier that the morphology of the sub-surface particulate structure is dependent on polymer-metal interaction. In the present studies, an inert polymer like polystyrene (PS) is blended with an interacting polymer P4VP. The optical studies on the silver particulate films deposited on softened blends of PS/P4VP have been carried out. The results show a shift in plasmon resonance to higher wavelength with increasing P4VP concentration of the blends in comparison to that of the films deposited on pure PS. An X-ray photoelectron spectroscopy study at two different electron take off angles indicates the formation of subsurface particulate structures for films deposited on blends.